The role of Twitter in accelerating engagement in alternative communicative spaces - Ošljak, Katja (Teorija in praksa, 2014)
The newly emerging communicative spaces on the Internet are vital to the research of power relations in society. The present text discovers how these relations are being challenged by engagement in alternative communicative spaces. More specifically, how Twitter is being used for accelerating this engagement. It highlights the activities of the Internet users who have been confronted with borders, limitations and even repressive and undemocratic environment. With the mixed method approach, we have gathered the quali- and quantitative data which uncovered the four dimensions of their engagement in alternative communicative spaces: 1) representation of opinions and information, 2) acquiring attention and consideration, 3) finding allies and engaging with influencers, 4) activation of community.
Keywords: Communication; Družbena omrežja; internet; Komuniciranje; komunikacijski prostor; Political engagement; Politična angažiranost; Social media